Catalyst for plasma-assisted ammonia cracking as well as preparation method and application of catalyst

By using catalysts composed of metals such as Ru, Ni, Fe, Co, and other metals in plasma ammonia catalytic cracking, combined with support such as FA, Al2O3, the problems of poor low-temperature activity and high-temperature inactivation of traditional catalysts are solved, and high-efficiency ammonia cracking is achieved The reaction simplifies the preparation process and improves stability.

CN119186589APending Publication Date: 2024-12-27XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308816.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the plasma-assisted ammonia catalytic cracking catalyst, traditional thermally catalytic ammonia cracking catalysts have problems such as low ammonia cracking efficiency, poor low temperature activity, high reaction temperature, and easy deactivation.

Method used

A catalyst with Ru as the promoter, Ni, Fe, Co as the active component, K, Na, Ba, Ce, La as the additive, FA, Al2O3, SiO2, MgO, CeO2, TiO2 as the support was developed, through Ultrasonic impregnation and segmented drying technology have improved the activity and stability of the catalyst and are suitable for low-temperature plasma ammonia catalytic cracking.

Benefits of technology

High ammonia conversion rate (>90%) is achieved under low temperature conditions (≤400℃), which reduces reaction temperature and energy consumption, improves the stability and dispersion of the catalyst, simplifies the preparation process, and avoids the H2 reduction and activation step .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005050051650000011
    Figure HDA0005050051650000011
  • Figure HDA0005050051650000012
    Figure HDA0005050051650000012
Patent Text Reader

Abstract

The invention provides a ruthenium (Ru)-started iron (Fe) / cobalt (Co) / nickel (Ni) metal catalyst capable of efficiently catalyzing ammonia cracking under the assistance of low-temperature plasma as well as a preparation method and application of the ruthenium (Ru)-started iron (Fe) / cobalt (Co) / nickel (Ni) metal catalyst. The ruthenium (Ru)-started iron (Fe) / cobalt (Co) / nickel (Ni) metal catalyst comprises a promoter, an active component, an auxiliary agent and a carrier. A small amount of precious metal and non-precious metal are loaded on a common metal oxide carrier through an ultrasonic impregnation method, the catalyst suitable for plasma-assisted ammonia catalytic cracking is developed through sufficient drying and high-temperature roasting, the prepared catalyst has high catalytic activity in a plasma-assisted ammonia catalytic cracking reaction, and the catalyst is suitable for industrial production. The low-temperature activity of the catalyst is better than that of conventional noble metal catalysts and non-noble metal catalysts, and the technology is lower in reaction temperature and lower in energy consumption compared with a traditional thermocatalysis technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of thermal catalysis technology and plasma catalysis technology in ammonia decomposition, and specifically relates to a catalyst for plasma-assisted ammonia catalytic cracking, and a preparation method and application thereof. Background Art

[0002] As a disposable energy, the excessive exploitation and use of fossil energy not only leads to the depletion of resources, but also aggravates environmental pollution. With the continuous growth of society's demand for energy, the development and application of zero-carbon new energy has become particularly urgent. Among many new energy sources, hydrogen energy has attracted widespread attention for its high calorific value, pollution-free and renewable characteristics. However, although hydrogen energy can be utilized in various forms such as hydrogen combustion and fuel cells, its large-scale promotion still faces technical bottlenecks. In particular, the safe and efficient storage and transportation of hydrogen have become key factors restricting the application of hydrogen energy. Therefore, in order to promote the rapid development of hydrogen energy, a storage and transportation medium that can achieve green and efficient storage and transportation and can quickly decompose to obtain hydrogen is needed to break through the limitations of existing technologies and promote the widespread application of hydrogen energy. Among them, in the field of hydrogen energy storage and transportation, ammonia as a hydrogen storage and transportation medium shows significant advantages and development prospects. Compared with direct storage and transportation of hydrogen, storing and transporting ammonia as a carrier for hydrogen storage and transportation has many advantages in the storage and transportation process. In the field of on-site rapid ammonia cracking regeneration hydrogen, ammonia cracking regeneration hydrogen technology has undergone decades of development, and its core lies in the research and development of innovative ammonia cracking technology and the development and preparation of efficient ammonia cracking catalysts. At present, the reaction temperature of thermal catalytic ammonia cracking is still relatively high, the ammonia conversion rate at low temperatures is low, the catalyst activity is limited, and there is little research on plasma-assisted ammonia catalytic cracking catalysts. In view of this situation, the purpose of the present invention is to provide a catalyst suitable for plasma-assisted ammonia catalytic cracking, which also has a high ammonia conversion rate in a lower temperature range.

[0003] Chinese patent document CN110270340A discloses an ammonia decomposition catalyst and its preparation method and application, wherein the main active components are Ni / Ru; the carrier is yttria-stabilized zirconia or BaCe 0.7 Zr 0.1 Y 0.2 O 3-δ The auxiliary agent is one or more of alkali metal oxides, alkaline earth metal oxides, and rare earth oxides; wherein Ni accounts for 5-15% of the catalyst, Ru accounts for 0.2-3% of the catalyst, and the auxiliary agent accounts for 2-10% of the catalyst. The catalyst disclosed in the patent is suitable for traditional thermal catalytic ammonia decomposition. When the reaction temperature is greater than or equal to 550°C, the ammonia decomposition rate can reach more than 95%. Although it is lower than the existing industrial catalyst working temperature of 800°C, its ammonia decomposition temperature is still relatively high, the catalytic activity is low, the processing capacity is low, the energy consumption is high, and the ammonia decomposition effect is poor.

[0004] Chinese patent document CN1506299A discloses a Ni-based catalyst for the decomposition of ammonia to produce hydrogen and nitrogen mixed gas, wherein the main active ingredient is Ni; the carrier is SiO2 or Al2O3; the auxiliary agent is one or more of IA, IIA, IIIB, VIII or rare earth elements in the periodic table; wherein the weight percentage of Ni is 1-40%. The catalyst is used for ammonia decomposition, and the use temperature of the catalyst is 650°C. Although the temperature is lower than that of the existing industrial ammonia decomposition catalyst, it is easy to sinter at high temperature. When the Ni loading is too high, its dispersibility is low, resulting in low catalytic activity and poor ammonia decomposition effect.

[0005] Chinese patent CN114570361A discloses a Ru-based catalyst for hydrogen production by decomposing ammonia and its preparation method, wherein the active metal is the precious metal Ru, and the carrier is a carbon layer coated with silicon dioxide; wherein the Ru content is 0.5-3wt%, and the preparation method of the carrier is to firstly carry out a hydrothermal reaction at 100°C for 24 hours, and then calculate to obtain a carbon-coated SiO2 composite carrier; after the carrier is prepared, Ru is loaded by an impregnation method, and the catalyst is obtained by drying and calcining. The catalyst carrier preparation method of the invention is cumbersome, and the ammonia conversion rate of the catalyst at a temperature of 500°C is only 61.8% at most, and its reaction temperature is still high, and the ammonia conversion rate is low. Summary of the invention

[0006] The present invention aims to solve a number of technical problems in the application of conventional thermal catalytic ammonia cracking catalysts in plasma-assisted ammonia catalytic cracking. These problems mainly include low ammonia cracking efficiency of the catalyst, poor low-temperature activity of ammonia cracking, poor effect of common thermal catalytic catalysts in plasma-catalyzed ammonia cracking, and easy deactivation under extreme conditions of high voltage and high current. In order to overcome these shortcomings, the present invention develops a catalyst suitable for plasma-assisted ammonia catalytic cracking, and provides a corresponding preparation method and application scheme.

[0007] The catalyst for plasma-assisted ammonia catalytic cracking provided by the present invention is composed of a promoter, an active component, an auxiliary agent and a carrier; the promoter Ru has a starting effect on the plasma-catalyzed ammonia cracking reaction and has a certain catalytic activity; the active component is one or more of Ni, Fe, and Co; the auxiliary agent is one of K, Na, Ba, Ce, and La; the carrier includes one or more of FA, Al2O3, La2O3, SiO2, MgO, CeO2, TiO2, and ZrO2.

[0008] The mass of the promoter Ru accounts for 0.1-15% of the total mass of the catalyst, the mass of each active metal of the active substance accounts for 5-20% of the total mass of the catalyst, the mass of the metal atoms of the auxiliary agent accounts for 2-18% of the total mass of the catalyst, and the rest is the proportion of the carrier.

[0009] The catalyst includes a promoter Ru whose mass accounts for 0.1-15% of the total mass of the catalyst;

[0010] The raw material of the promoter Ru is one of ruthenium chloride hydrate, ruthenium acetate and ruthenium nitrate hydrate.

[0011] The active components of the catalyst include one or more of Ni, Fe, and Co, and the mass of each active metal accounts for 5-20% of the total mass of the catalyst;

[0012] The raw materials of the active metals Fe, Co and Ni are respectively one of their corresponding chloride hydrates, nitrate hydrates and acetate hydrates.

[0013] The catalyst promoter includes one or more of K, Na, Ba, Ce, and La, and the atomic mass of each substance accounts for 2-18% of the total mass of the catalyst;

[0014] The raw material of the auxiliary agent is one of the corresponding hydroxides, oxides, nitrates, nitrate hydrates, chlorates, and chlorate hydrates.

[0015] The catalyst carrier includes one or more of FA, Al2O3, La2O3, SiO2, MgO, CeO2, TiO2, and ZrO2, and the mass percentage of the carrier is the total mass percentage of the catalyst minus the mass percentage of the promoter, active metal, and additive.

[0016] The preparation method of the ammonia cracking catalyst for plasma catalysis comprises:

[0017] (1) dissolving the initiator metal salt hydrate RuCl3·6H2O, the active component metal salt hydrate, the auxiliary metal, and the rare earth nitrate hydrate in a certain amount of ultrapure water, and stirring them fully at room temperature to completely dissolve them to prepare a metal salt mixed solution;

[0018] (2) Weighing a corresponding mass of the carrier, adding the carrier to the metal salt mixed solution and stirring it thoroughly to make it preliminarily mixed, and then continuously stirring it under ultrasonic conditions to make it fully impregnated;

[0019] (3) first transferring the impregnated product to a 105°C forced air drying oven for drying for 3-4 hours, stirring the dried solid to make it fluffy; then placing the stirred fluffy solid in a 70 or 75°C forced air drying oven for drying for 4-12 hours to allow it to be fully oxidized during the drying process;

[0020] (4) Transferring the dried catalyst to a muffle furnace for high-temperature calcination, setting the muffle furnace to perform a temperature program at a heating rate of 10°C / min, from room temperature to the calcination temperature. The calcination temperature is 500-850°C, the calcination time is 2-4h, and the calcination is naturally cooled to room temperature after the calcination is completed;

[0021] (5) grinding and screening the calcined catalyst;

[0022] (6) The prepared catalyst is diluted with an inert carrier (FA, Al2O3, La2O3, SiO2, MgO, CeO2, TiO2, ZrO2) according to a mass ratio to obtain an ammonia cracking catalyst.

[0023] The present invention provides a Ru-started Fe / Co / Ni-based multi-metal ammonia cracking catalyst and a preparation method and application thereof. The catalyst includes a promoter, an active component, an auxiliary agent and a carrier. The promoter is Ru, which has a certain activity in starting the plasma-assisted ammonia catalytic cracking reaction; the active component is one or more of Ni, Fe, and Co, and the auxiliary agent is one or more of K, Na, Ba, Ce, and La; the carrier includes one or more of FA, Al2O3, La2O3, SiO2, MgO, CeO2, TiO2, and ZrO2. The promoter of the catalyst plays a bridging role in the ammonia catalytic cracking reaction process, enhances the activity of the active component, improves the electron transfer ability of the catalyst carrier, can start the plasma-assisted ammonia catalytic cracking reaction at low temperature, and has a certain ammonia cracking activity at low temperature; the active substance provides a large number of active sites for the reaction; the auxiliary agent mainly modifies and disperses the catalyst active substance and the promoter, increases the dispersibility of each component on the surface of the carrier, strengthens the catalyst electron transfer ability and enhances the interaction between the components, and further improves the catalyst activity. The promoter, active substance, auxiliary agent and carrier interact with each other, which enhances the activity of plasma-assisted ammonia catalytic cracking reaction under low temperature conditions, while reducing the ammonia cracking temperature and energy consumption.

[0024] The catalyst is characterized by a high specific surface area and good electron transfer ability, does not require H2 reduction activation, and has high ammonia cracking activity under low temperature conditions (≤400°C).

[0025] The present invention develops a low-temperature and efficient plasma-assisted ammonia catalytic cracking catalyst. In the catalyst preparation process, by adopting ultrasonic impregnation technology, the metal can be evenly loaded on the carrier in a short time, which significantly shortens the impregnation time. At the same time, the catalyst is dried by a staged drying method, which not only accelerates the drying rate, but also allows the catalyst to be fully oxidized during the drying process, further shortening the drying time. In the development and preparation of the catalyst, the present invention comprehensively considers multiple factors such as plasma properties, ammonia cracking mechanism and catalyst properties. Special attention is paid to the catalytic properties of precious metal and non-precious metal catalysts (although precious metal catalysts have high low-temperature activity, they have limited active sites at low loadings; and although non-precious metal catalysts have low low-temperature activity, they can provide abundant active sites during the reaction process). Based on the above considerations, the present invention has developed a catalyst suitable for low-temperature plasma catalytic ammonia cracking, which provides new ideas and preparation methods for the development and research of low-temperature plasma-assisted catalytic ammonia cracking reaction catalysts.

[0026] Compared with the existing catalyst and its preparation technology, the present invention has the following advantages:

[0027] (1) The catalyst prepared by the present invention starts the non-precious metal catalytic ammonia cracking reaction through precious metals, which reduces the amount of precious metals used. At the same time, at a relatively low temperature (400°C), its catalyst activity is equivalent to that of a high-loaded precious metal catalyst (ammonia conversion rate>90%). This is due to the addition of non-precious metals and additives, which not only enhances the conductivity of the catalyst carrier, but also improves the electron transfer ability of the catalyst while ensuring that the metal is highly dispersed. In addition, non-precious metals can also provide abundant active sites for the initiated ammonia cracking reaction, thereby effectively promoting the progress of the ammonia cracking reaction.

[0028] (2) The present invention develops a catalyst suitable for plasma-assisted ammonia catalytic cracking, which exhibits excellent low-temperature activity and effectively improves the catalytic cracking efficiency.

[0029] (3) The preparation process of the catalyst in the present invention is simple and fast, with a short cycle and easy operation.

[0030] (4) The catalyst prepared by the present invention exhibits excellent ammonia cracking activity without the need for prior H2 reduction activation and can be directly applied to the ammonia cracking process.

[0031] (5) The catalyst of the present invention does not need to be washed or filtered during the preparation process, which ensures the accuracy of the catalyst loading and avoids the cumbersome operation steps of multiple loadings. At the same time, the absence of washing and filtering also eliminates the generation and discharge of waste liquid, thus achieving an efficient and environmentally friendly preparation process for the catalyst.

[0032] (6) The catalyst of the present invention exhibits high catalytic stability in a high voltage, high current, and long-term plasma environment, ensuring efficient and stable operation of the ammonia catalytic cracking process.

[0033] (7) The catalyst preparation process of the present invention adopts a cooling and segmented drying method to ensure that the catalyst is fully oxidized during the drying process while maintaining its highly dispersed state, thereby improving the catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 In Example 1, Ru 0.025 Ni 0.1 Ce 0.1 / Al2O3 catalyst diluted with Al2O3 in different proportions at 100-400℃.

[0035] Figure 2 A dotted line graph showing the ammonia cracking conversion rate at 100-400°C after the catalysts of Example 2, Example 3, Example 4 and Example 5 were diluted with an equal mass of Al2O3. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is further described below in conjunction with some embodiments.

[0037] Example 1: Ru 0.025 Ni 0.1 Ce 0.1 / Al2O3 catalyst

[0038] Preparation scheme of the catalyst: weigh 0.38g RuCl3·6H2O, 2.97g Ni(NO3)3·6H2O, 1.86g Ce(NO3)3·6H2O, and 4.65g Al2O3, put the weighed metal salts into a beaker, add 10mL ultrapure water, stir thoroughly to dissolve them, and prepare a metal salt mixed solution; add the weighed Al2O3 into the metal salt mixed solution and stir, stirring while ultrasonicating for 15 minutes; after the impregnation is completed, dry it in a 105°C blast oven for 4 hours, take out the catalyst and stir it until it is fluffy, and then dry the stirred fluffy catalyst in a 70°C blast oven for 3 hours; after the drying is completed, transfer the catalyst to a muffle furnace for calcination, set the muffle furnace program to heat up from 30°C to 650°C in 60 minutes, and calcine at a high temperature of 650°C for 2 hours. After the calcination is completed, wait for the temperature to naturally drop to room temperature before taking out the catalyst; grind and sieve to obtain a pure catalyst. Finally, Al2O3 is weighed according to the required mass ratio and mixed evenly to obtain a plasma catalytic ammonia cracking catalyst.

[0039] Plasma-assisted ammonia catalytic cracking test method: the catalyst Ru 0.025 Ni 0.1 Ce 0.1 / Al2O3:Al2O3=1:1;1:2;1:3;1:5;1:10;mix and prepare; the catalysts prepared above were subjected to plasma-assisted ammonia catalytic cracking experiments respectively, and the total amount of catalyst used in the ammonia cracking experiment was 1g. The specific operation of the experiment was as follows: first fill 1g of catalyst into a quartz tube and block it with quartz wool; the plasma power input power was 30-31W, the inlet NH3 flow rate was 30mL / min, and the ammonia cracking experiment was carried out at 100℃, 150℃, 200℃, 250℃, 300℃, 350℃, and 400℃ respectively; before starting the activity test at each temperature section, the equipment should be purged with Ar (30mL / min) for 10min, and the residual ammonia at the reactor outlet should be absorbed with dilute sulfuric acid, and then the mixed gas of hydrogen and nitrogen should be dried with a drying tube, and then the mass flow rate of the mixed gas should be measured.

[0040] The above-mentioned activity evaluation method was used to evaluate the activity of the catalyst using pure ammonia gas. The catalyst was 60-80 mesh, loaded with 1g, and the reaction space velocity was 3600-20000mL / (g·h). According to the formula:

[0041] Ammonia decomposition rate x = outlet nitrogen and hydrogen flow / (2 × inlet ammonia flow) × 100%

[0042] Calculate the decomposition rate of ammonia. The results are shown in the attached Figure 1 .

[0043] Example 2: Ru 0.025 Fe0.1 Ce 0.1 / Al2O3:Al2O3 catalyst

[0044] Same as Example 1, except that during the catalyst preparation process, 2.97 g Ni(NO3)3·6H2O was replaced by 4.34 g Fe(NO3)3·9H2O Fe hydrated nitrate salt, and the loading amount was 10%; the obtained catalyst was marked as Ru 0.025 Fe 0.1 Ce 0.1 ; The reaction space velocity is 3600mL / (g·h), and the experimental method is the same as Example 1.

[0045] Example 3: Ru 0.025 Co 0.1 Ce 0.1 / Al2O3:Al2O3 catalyst

[0046] Same as Example 1, except that during the catalyst preparation process, 2.97 g Ni(NO3)3·6H2O was replaced with 1.86 g Co(NO3)2·6H2O, and the obtained catalyst was marked as Ru 0.025 Co 0.1 Ce 0.1 / Al2O3; the reaction space velocity is 3600mL / (g·h), and the experimental method is the same as that in Example 1.

[0047] Example 4: Ru 0.025 Ni 0.1 Ce 0.1 / SiO2 catalyst

[0048] Same as Example 1, except that during the catalyst preparation process, the carrier 4.65 g Al2O3 was replaced with 4.65 g SiO2, and the obtained catalyst was marked as Ru 0.025 Ni 0.1 Ce 0.1 / SiO2; the reaction space velocity is 3600mL / (g·h), and the experimental method is the same as that in Example 1.

[0049] Example 5: Ru 0.1 Ce 0.1 / Al2O3 catalyst

[0050] Same as Example 1, except that during the catalyst preparation process, the amount of RuCl3·6H2O was increased from 0.38 g to 1.53 g, i.e., 2.5% to 10% of the catalyst, and the catalyst obtained by adding no Ni metal nitrate hydrate was marked as Ru 0.1 Ce 0.1 / Al2O3; the reaction space velocity is 3600mL / (g·h), and the experimental method is the same as that in Example 1.

[0051] Plasma-assisted ammonia catalytic cracking reaction experiments were carried out on the catalysts of Examples 1 to 5 at various temperatures in the range of 100 to 400°C, and the results are shown in [Table 1] and the attached Figure 1 and attached Figure 2 middle.

[0052] [Table 1] Catalyst activity evaluation results in Examples 1-5

[0053]

[0054] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A catalyst for plasma-assisted ammonia catalytic cracking and its preparation method and application, (1) the catalyst is characterized by The catalyst comprises a promoter, an active component, an auxiliary agent and a carrier; the promoter is Ru; the active component is one or more of Fe / Co / Ni; the auxiliary agent is one of potassium (K), sodium (Na), barium (Ba), cerium (Ce) and lanthanum (La); the carrier is one or more of FA (fly ash), aluminum oxide (Al2O3), lanthanum oxide (La2O3), silicon oxide (SiO2), magnesium oxide (MgO), cerium oxide (CeO2), titanium oxide (TiO2) and zirconium oxide (ZrO2). (2) The preparation method of the catalyst mainly comprises: firstly dissolving the metal salts corresponding to the promoter, active substance and auxiliary agent in ultrapure water to obtain a mixed solution of metal salts; then using an ultrasonic impregnation method to uniformly load the promoter, active component and auxiliary agent on the carrier; after the impregnation is completed, the impregnated material is cooled and dried in stages, roasted, ground and screened to finally obtain a catalyst. (3) The application of the catalyst is the application of the catalyst in catalytic ammonia cracking in thermal catalysis and plasma environment.

2. The plasma-assisted ammonia catalytic cracking catalyst described in claim 1 is characterized as follows: The mass of the promoter Ru accounts for 0.1-15% of the total mass of the catalyst; the mass of each active metal of the active substance accounts for 5-20% of the total mass of the catalyst; the total mass of the auxiliary metal atoms accounts for 2-18% of the total mass of the catalyst; the rest is the mass proportion of the carrier; The promoter Ru, whose raw material is one of ruthenium chloride hydrate, ruthenium acetate and ruthenium nitrate hydrate; The raw materials of the active metals Fe / Co / Ni are respectively one of the corresponding chloride hydrates, nitrate hydrates and acetate hydrates; The raw material of the auxiliary agent is one of the corresponding hydroxides, oxides, nitrates, nitrate hydrates, chlorates, and chlorate hydrates.

3. The method for preparing the catalyst according to claim 1 is characterized in that: (1) dissolving a certain amount of promoter, active component, auxiliary metal and rare earth metal salt hydrate in a certain amount of ultrapure water, and stirring them fully at room temperature to completely dissolve them to prepare a metal salt mixed solution; (2) weighing a corresponding amount of the carrier, adding the carrier to the metal salt mixed solution and stirring it thoroughly to make it preliminarily mixed, and then continuously stirring it under ultrasonic conditions to make it fully impregnated; (3) The stepwise drying step of claim 1 is as follows: first, the impregnated product is transferred to a 105°C forced air drying oven for drying for 3-4 hours, and then the dried solid is stirred to make it fluffy; then, the stirred fluffy solid is placed in a 70°C or 75°C forced air drying oven for drying for 4-12 hours to allow it to be fully oxidized during the drying process; (4) Transferring the dried catalyst to a muffle furnace for high-temperature calcination, the temperature of the muffle furnace is increased at a rate of 10°C / min, from room temperature to the calcination temperature. The calcination temperature is 500-850°C, the calcination time is 2-4h, and the catalyst is naturally cooled to room temperature after the calcination is completed; (5) grinding and screening the calcined catalyst; (6) The prepared catalyst is finally diluted with an inert carrier (FA, Al2O3, La2O3, SiO2, MgO, CeO2, TiO2, ZrO2) according to the mass ratio so that the catalyst powder is evenly dispersed in space, thereby increasing the effective reaction volume and increasing the residence time of ammonia.

4. Application of the catalyst according to claims 1 to 3 and the catalyst prepared by the preparation method in the field of thermal catalysis and plasma catalysis ammonia cracking.